2015
DOI: 10.1186/s12891-015-0704-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-impregnated cement spacer as definitive management for osteomyelitis

Abstract: BackgroundOsteomyelitis is a challenge for orthopaedic surgeons. There is a lack of scientific evidence to guide treatment. The purpose of this study was to report the clinical outcome of unplanned retention of antibiotic-impregnated cement spacer (ACS) in the management of osteomyelitis.MethodsEight patients (7 with tibial infections and 1 with a calcaneal infection) with osteomyelitis received radical debridement and insertion of an ACS into the bone defect as the definitive management. The mean follow-up pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 15 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…Insertion of antibiotic-loaded bone cement along with débridement are initial surgical treatment options for pyogenic or tuberculosis bone or joint infections to control active infection before further treatments such as arthrodesis, resection arthroplasty, or prosthetic replacement [25,32,42]. Some studies have shown the effectiveness of antibiotic-loaded bone cement in pyogenic osteomyelitis [14,29,40,45], while other studies have shown the effectiveness of antibiotic-loaded bone cement in tuberculosis osteomyelitis or arthritis [20,25,32,42]. Furthermore, there is little information regarding combinations of antibiotics or their mixture ratios with bone cement [23,30,31,38].…”
Section: Introductionmentioning
confidence: 99%
“…Insertion of antibiotic-loaded bone cement along with débridement are initial surgical treatment options for pyogenic or tuberculosis bone or joint infections to control active infection before further treatments such as arthrodesis, resection arthroplasty, or prosthetic replacement [25,32,42]. Some studies have shown the effectiveness of antibiotic-loaded bone cement in pyogenic osteomyelitis [14,29,40,45], while other studies have shown the effectiveness of antibiotic-loaded bone cement in tuberculosis osteomyelitis or arthritis [20,25,32,42]. Furthermore, there is little information regarding combinations of antibiotics or their mixture ratios with bone cement [23,30,31,38].…”
Section: Introductionmentioning
confidence: 99%
“…9 Bone resorption is another concern associated with retained spacers and has been reported in the setting of infected hip replacements; however, this may not be the case in long bones because of the spacer being immobile. 10 We did not notice any notable resorption.…”
Section: Discussionmentioning
confidence: 65%
“…It is a challenging task to treat orthopaedic implant infections that may lead to implant exchange and, in severe cases, may results in amputation and mortality [1] . Infections in surgical site are the third most commonest in cause of infection in surgical patients [2] . Infection is when pus is present in the wound or there is discharge that yields growth of pathogenic micro-organisms on culture.…”
Section: Introductionmentioning
confidence: 99%
“…In implant surgery when device is not exposed, infection is taken as a superficial but when the implant is exposed, it is deep infection [3] . Some factors such as advanced age, concomitant infection elsewhere in the body, use of systemic steroids, smoking, alcohol, and transfusion of certain blood products also increases the risk of infection [2] . Staphylococcus aureus is the most frequent pathogen implicated in post-surgical infections [4] .…”
Section: Introductionmentioning
confidence: 99%